Prevalence of sexually transmitted infections and human papillomavirus in cervical samples from incarcerated women in São Paulo, Brazil: a retrospective single-center study - Zonta, Marco A.; Liljander, Anne; Roque, Karina B.; Schillert, Arne; Kai, Marco; dos Santo, Flávia A.; de Freitas, Giulia Pinheiro; Soane, Michel; Cavalar, Markus; Janaudis, Gustavo; Shio, Marina Tiemi (Frontiers in Public Health, 2024)
Introduction Sexually transmitted infections (STIs) cause considerable morbidity worldwide and, depending on the specific pathogen, may lead to serious complications in the female reproductive tract. Incarcerated women are particularly vulnerable to health problems with a disproportionate high rate of STIs, including infections with human papillomavirus (HPV). Methods Here, cervical swab samples collected from 299 women (18 to 64 years) living in one of the women’s prisons of São Paulo, Brazil were submitted for liquid-based cytology to determine the prevalence of precancerous lesions. Furthermore, direct detection of 30 genital HPV genotypes (18 high-risk and 12 low-risk types) and 11 additional STIs (Chlamydia trachomatis, Neisseria gonorrhoeae, Herpes simplex virus 1 and 2, Haemophilus ducreyi, Mycoplasma genitalium and hominis, Treponema pallidum, Trichomonas vaginalis, Ureaplasma parvum and urealyticum) were performed by molecular typing using two PCR-based DNA microarray systems, i.e., EUROArray HPV and EUROArray STI (EUROIMMUN), respectively. Results The overall prevalence of cytological abnormalities was 5.8%, including five women with low-grade and five women with high-grade squamous intraepithelial lesions. The overall prevalence of HPV was 62.2, and 87.1% of the HPV-positive women were infected with oncogenic high-risk (HR) HPV types. HPV types 16 (24.1%), 33 and 52 (both 10.4%) were the most frequently detected. The prevalence of the other STIs was 72.8%. Up to four different pathogens were found in the infected women, the most frequent being Ureaplasma parvum (45.3%), Mycoplasma hominis (36.2%) and Trichomonas vaginalis (24.8%). Conclusion The high number of HR-HPV infections and other STIs described here highlights the fact that the Brazilian female prison population requires more attention in the country’s health policies. The implementation of screening programs and treatment measures might contribute to a decrease in the incidence of STIs and cervical cancer in this vulnerable population. However, for such measures to be effective, further studies are needed to investigate the best practice to get more women to engage in in-prison prevention programs, e.g., through offering further sexual health education and self-sampling.